The Laws of Thermodynamics : A Very Short Introduction - Atkins, Peter (Oxford, New York Oxford University Press, 2010)
Among the many laws of science, there are four laws that direct and constrain everything that happens in the Universe. From the sudden expansion of a cloud of gas to the unfurling of a leaf they help us understand the course of life itself. In this Very Short Introduction Peter Atkins' explains what the four laws are and how they work.
Include Index and Illustration
Keywords: Physical laws -- Laws of thermodynamics -- Thermodynamics